Remote control car starter (RCCS) - Mohammad Akmal, Akashah (2006)
This project is to develop a remote control car starter. The use of this project will be able to start the car remote in a distance range. This project consist two important parts which is transmitter and receiver. When a signal has been detected at the transmitter, the transmitter will send the data to microcontroller and thus bypass the connection in the car (output from relay). The microcontroller that has been used in this project is PIC16F84.Today’s fast paced technological developments strive to make our lives comfortable. For example, with the low temperatures in morning and the hot temperatures in the afternoon, drivers suffer while waiting for their car to heat up or cool down. Other reasons such as proper operation and protection from freezing of the engine brought forth the development of the remote engine starter.